Studi Wawancara Persepsi Guru Terhadap Penerapan Model Project Based Learning pada Pembelajaran IPA - Eka Daniatul Khoiriyah; Tantri Rahma Wati; Refa Regia Andini; Addiena Mutiara Hasnim; Luluk Atun Nasihah; Eka Puspita Kartika Sari (STKIP HARAPAN BIMA, 2026)
This study aims to analyze science teachers’ perceptions of the implementation of Project Based Learning (PjBL) in junior high schools located in resource-limited areas. This research employed a descriptive qualitative design. The instruments used were semi-structured interview guidelines and documentation sheets. Data were collected through in-depth interviews and document analysis. Data analysis was conducted using data reduction, categorization, thematic analysis, data display, and conclusion drawing. Data validity was ensured through source and document triangulation. The results show that teachers generally have positive perceptions of PjBL as it enhances students’ intrinsic motivation, active engagement, and critical thinking skills. However, challenges include limited instructional time, inadequate facilities, students’ readiness for independent learning, and the complexity of authentic assessment. It is concluded that PjBL can effectively improve science learning when supported by careful planning, continuous teacher professional development, and adequate facilities.